(untitled) (Journal of Economic Research & Business Administration, 2017)
Tax regulation is a measure of the indirect impact on elements such as economy, social and political processes which is made by the introduction or abolition of taxes, tax rates change, the establishment of tax incentives and other measures of indirect impact. It is important for the economy of Kazakhstan to develop innovation as scientific and technological progress is one of the main factors of economic growth, therefore, special attention should be given for its state support. Successful development of innovations in Kazakhstan can be supported by the optimizing tax stimulants which can be represented by the tax benefits, the creation of economic zones and decreasing the tax burden for persons engaged in innovative activities. In this article the author conducted a study using tax stimulants in innovation. The author has analyzed the tax rules governing innovation activities. The development state and the state involvement in innovation, recommendations to improve the tax stimulants are also studied in innovation activities.